Elite athletes: Are the genes the champions? - Lucia, A.; Moran, M.; Zihong, H.; Ruiz, J. R. (International Journal of Sports Physiology and Performance, 2010)
Recent research has analyzed the genetic factors that influence world-class athletic status. Much of what we know comes from association studies, with the ACE I/D and ACTN3 R577X polymorphisms having been extensively studied. The association between the ACTN3 R577X variation and elite athlete status in power sports is strongly documented, yet whether the current body of knowledge on other variants can be extrapolated to athletic champion status remains to be determined. Athletic champion status is a complex polygenic trait in which numerous candidate genes, complex gene-gene interactions, and environment-gene interactions are involved. Besides the need for more studies and new approaches taking into account the complexity of the problem, we believe that factors beyond genetic endowment are likely to have a stronger influence in the attainment of athletic champion status.